2015
DOI: 10.2350/14-08-1539-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Gonadoblastoma in Patients with Ullrich-Turner Syndrome

Abstract: Ullrich-Turner syndrome (UTS) is a common chromosomal abnormality caused by partial or complete X chromosome monosomy. One half of the patients have a 45,X karyotype, whereas the remaining patients display other X chromosome anomalies. In 6% to 11% of UTS, a normal or partly deleted Y chromosome has been found. A 10% to 30% risk of developing gonadoblastoma was found in the latter patients. The aim of this study was to evaluate the prevalence of Y chromosome-derived material, the occurrence of gonadoblastoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 31 publications
0
19
0
3
Order By: Relevance
“…Another study published recently reported 35.3% incidence of gonadoblastoma 28. Twenty patients with TS had Y-chromosome sequences from a total of 217 and 17 of them underwent gonadectomy 28. An even higher frequency was reported by Alvarez-Nava et al29 who investigated 52 patients and detected four with Y-chromosome sequences (7.7%), all underwent gonadectomy and two had gonadoblastoma (50%).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Another study published recently reported 35.3% incidence of gonadoblastoma 28. Twenty patients with TS had Y-chromosome sequences from a total of 217 and 17 of them underwent gonadectomy 28. An even higher frequency was reported by Alvarez-Nava et al29 who investigated 52 patients and detected four with Y-chromosome sequences (7.7%), all underwent gonadectomy and two had gonadoblastoma (50%).…”
Section: Discussionmentioning
confidence: 83%
“…In the two patients with gonadoblastoma alone, age at surgery was 1.5 and 11.7 years 6. Another study published recently reported 35.3% incidence of gonadoblastoma 28. Twenty patients with TS had Y-chromosome sequences from a total of 217 and 17 of them underwent gonadectomy 28.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The other case involved a 14-year-old TS patient with findings of bilateral gonadoblastoma and a mixed dysgerminoma and embryonal carcinoma [Zelaya et al, 2015]. The patient had a Y chromosome mosaicism, and interphase FISH analysis showed Y chromosomal material in the gonadal tissue; thus, the development of the tumor could be explained by the presence of Y chromosomal material.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonal carcinoma is, however, a very rare event in TS without Y chromosomal material and has to our knowledge only been described once in a patient with putative 45,X [Soh et al, 1992], while a mixed dysgerminoma and embryonal carcinoma was described in another patient [Zelaya et al, 2015].…”
mentioning
confidence: 99%